Двухдиапазонный усилитель на поверхностных и объемных волнах субтерагерцового диапазона - Одаренко, Е. Н.; Шматько, А. А.; Юдинцев, П. В. (Weber Co., 2011)
The subterahertz amplifier with two input signals is considered. Theoretical analysis is performed on the basis of nonlinear multidimensional theory of the beam-wave interaction. Conditions of the regenerative amplification and locking on the first and third harmonics of the surface wave frequency are obtained.
Keywords: субтерагерцовый диапазон; двухрежимный прибор О-типа; поверхностные волны